Class Action Research: Application of the Sociodrama Method in Increasing Student Learning Motivation - Tanjung, Abdul Rahman; Ridho, Muhammad Rasyid (Journal of Islamic Education and Ethics, 2024)
Classroom action research is a teacher's effort to solve problems that arise in the classroom environment and as a means of assessing the learning process. This study aims to find out how the application of Sociodrama increases student learning motivation, as well as the results of the application of the Sociodrama method in increasing student learning motivation. Regarding the implementation of learning in the classroom, it is known that the daily test scores of the Islamic Cultural History subject are for 45 students, and for those who have fulfilled the KKM, as many as 21 students or 47.73%. Meanwhile, those who have not reached KKM are 23 students, or 52.27%. This study used Classroom Action Research (PTK) conducted on grade VIII students of SMP Muhammadiyah Tebing Tinggi City for the 2023-2024 school year. The results of the study In the first cycle, the presentation of student learning activities at each meeting increased with an average student learning activity of 52.856%. This proves that the first cycle has not reached the expected target because learning will be declared successful if student activities reach the target of 80%. It is necessary to make improvements by continuing the second cycle of learning. In cycle II, the percentage of student learning activities at each meeting increased, averaging 74.285%. Thus, learning activities applying the Sociodrama as a learning method have reached the target with a success indicator of 80%. Therefore, there was an increase in learning motivation for grade VIII students in the Islamic Cultural History Subject.